168k views
21 votes
Find
(d^2y)/(dx^2) if
x^2y^2=1

Options:

A.
(2y)/(x^2)
B. 0
C.
(y)/(x)
D.
(-y)/(x)
E.
(-y)/(x^2)

User Muszeo
by
5.4k points

1 Answer

7 votes

Answer:

A)
(d^2y)/(dx^2)=(2y)/(x^2)

Explanation:

Use implicit differentiation to find dy/dx


x^2y^2=1\\\\(d)/(dx)(x^2y^2)=(d)/(dx)(1)\\ \\x^2((d)/(dx)y^2)+((d)/(dx)(x^2))y^2 =0\\\\2yx^2(dy)/(dx)+2xy^2=0\\\\2xy(x(dy)/(dx)+y)=0\\ \\x(dy)/(dx)+y=0\\ \\x(dy)/(dx)=-y\\ \\(dy)/(dx)=-(y)/(x)

Determine d²y/dx² using dy/dx


(dy)/(dx)=(-y)/(x)\\ \\ (d^2y)/(dx^2)=((x)[(d)/(dx)(-y)]-(-y)[(d)/(dx)(x)] )/(x^2)\\ \\ (d^2y)/(dx^2)=(-x(dy)/(dx)+y)/(x^2)\\ \\ (d^2y)/(dx^2)=(-x((-y)/(x))+y)/(x^2)\\\\ (d^2y)/(dx^2)=(-(-y)+y)/(x^2)\\\\ (d^2y)/(dx^2)=(y+y)/(x^2)\\\\ (d^2y)/(dx^2)=(2y)/(x^2)

Helpful tips

  • When doing implicit differentiation, make sure to treat "y" as a constant and write dy/dx next to the y-term because it's differentiated with respect to x
  • The product rule is
    (d)/(dx)[f(x)g(x)]=f(x)[(d)/(dx)g(x)]+[(d)/(dx)f(x)]g(x)
  • The quotient rule is
    (d)/(dx)[(f(x))/(g(x))]=(f(x)[(d)/(dx)g(x)]-g(x)[(d)/(dx)f(x)])/((g(x))^2)

  • (dy)/(dx) represents the first derivative of y with respect to x and
    (d^2y)/(dx^2) represents the second derivative of y with respect to x

Let me know if you have any more questions!

User Lindauson
by
5.4k points